1997
DOI: 10.1254/jjp.75.447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Soybean Lecithin Transphosphatidylated Phosphatidylserine on Impaired Learning of Passive Avoidance in Mice

Abstract: ABSTRACT-Soybean lecithin transphosphatidylated phosphatidylserine (SB-tPS) was investigated for its effect on the impaired learning of a passive avoidance task by mice induced by scopolamine or cyclohex imide. SB-tPS (240, 360, 480 mg/kg) administered orally significantly prolonged the step-through latency shortened by scopolamine. SB-tPS (240 mg/kg) administered orally also prolonged the step-through latency shortened by cycloheximide. These results suggest that the effect of SB-tPS on the impaired learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It has been confirmed that SB-tPS does not alter the pain threshold of mice in the hot plate test (9). In addition, as mentioned above, SB-tPS did not affect any parameters in the open-field test ( Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…It has been confirmed that SB-tPS does not alter the pain threshold of mice in the hot plate test (9). In addition, as mentioned above, SB-tPS did not affect any parameters in the open-field test ( Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…An alternative for supplying PS is transphosphatidylation, in which the polar head group of lecithin (such as soybean lecithin) is exchanged with L-serine by phospholipase D (PLD) (6,7). The pharmacological effects of PS enzymatically synthesized from soybean lecithin were confirmed using several experimental animals (8)(9)(10).…”
mentioning
confidence: 99%
“…Also, other experiments have shown an improvement in memory, learning capacity, and other cognitive parameters in PS-supplemented rodents [7][8][9][10][11]. This is plausible, since PS was found to stimulate neurotransmitter release [7,12], increase brain glucose metabolism [13,14] and reduce oxidative stress in the brain [15].…”
Section: Phosphatidylserine (Ps) and Phosphatidic Acid (Pa) In Memorymentioning
confidence: 87%